Ultrasound-guided parasternal intercostal nerve block for postoperative analgesia in mediastinal mass resection by median sternotomy: a randomized, double-blind, placebo-controlled trial - Hexiang Chen; Wenqin Song; Wei Wang; Yawen Peng; Chunchun Zhai; Lihua Yao; Zhongyuan Xia (BMC Anesthesiology, 2021)
Abstract Background Ultrasound-guided parasternal intercostal nerve block is rarely used for postoperative analgesia, and its value remains unclear. This study aimed to evaluate the effectiveness of ultrasound-guided parasternal intercostal nerve block for postoperative analgesia in patients undergoing median sternotomy for mediastinal mass resection. Methods This randomized, double-blind, placebo-controlled trial performed in Renmin Hospital, Wuhan University, enrolled 41 participants aged 18–65 years. The patients scheduled for mediastinal mass resection by median sternotomy were randomly assigned were randomized into 2 groups, and preoperatively administered 2 injections of ropivacaine (PSI) and saline (control) groups, respectively, in the 3rd and 5th parasternal intercostal spaces with ultrasound-guided (USG) bilateral parasternal intercostal nerve block. Sufentanil via patient-controlled intravenous analgesia (PCIA) was administered to all participants postoperatively. Pain score, total sufentanil consumption, and postoperative adverse events were recorded within the first 24 h. Results There were 20 and 21 patients in the PSI and control group, respectively. The PSI group required 20% less PCIA-sufentanil compared with the control group (54.05 ± 11.14 μg vs. 67.67 ± 8.92 μg, P < 0.001). In addition, pain numerical rating scale (NRS) scores were significantly lower in the PSI group compared with control patients, both at rest and upon coughing within 24 postoperative hours. Postoperative adverse events were generally reduced in the PSI group compared with controls. Conclusions USG bilateral parasternal intercostal nerve block effectively reduces postoperative pain and adjuvant analgesic requirement, with good patient satisfaction, therefore constituting a good option for mediastinal mass resection by median sternotomy.